Experimental Study on the Effect and Mechanism of Chemical Stimulation on Deep High-Temperature Granite - Cui, Zhenpeng; Shangguan, Shuantong; Gherardi, Fabrizio; Qi, Xiaofei; Xu, Jianan; He, Siqing; Feng, Bo (Frontiers in Earth Science, 2022)
Chemical stimulation has been increasingly applied to improve the performance of geothermal reservoirs since early 1980’s. The potential for the successful application of this technique to high-temperature reservoirs hosted in granitic rocks is still uncertain, and one of the keys to assess this potential is to investigate experimentally the geochemical reactivity induced via chemical stimulation on relevant rock specimens. On this premise, we combined high-temperature and high-pressure dynamic simulation and static corrosion experiments to explore the effect of different chemical stimulants on the permeability of granite samples from the Baimiao formation (Hebei Province, China). Experimental results show that NaOH-dominated alkaline stimulants cause only weak dissolution patterns on primary feldspars and quartz, and do not sensitively affect the original amount of chlorite. The overall effect is a negligible enhancement of the original permeability of all the granite specimens analyzed. Conversely, a large increase in permeability is observed when an acid mixture of 10wt% HCl + 1.5wt% HF is used as stimulant, with an observed maximum magnifying effect of about 27 times, due to the effective dissolution of feldspar and chlorite. Though quartz appears not to be affected by dissolution, a relatively large amount of secondary neo-formed amorphous silica is also documented.